PENGEMBANGAN CANDI MERAK SEBAGAI DESTINASI WISATA DI KABUPATEN KLATEN - Bezaleel Yuhen Punto Adi Esthiyanto; I Wayan Srijaya; Ida Bagus Sapta Jaya (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This article discusses the development of Merak Temple as a tourist destination. Merak Temple is a temple left over from the Ancient Mataram Kingdom era which was built in the 8th to 9th centuries, located in Karangnongko Village, Klaten Regency. The aim of this research is to determine the potential of Merak Temple and the strategy for developing Merak Temple as a tourist destination in Klaten Regency. The method used is a descriptive method. The analysis used is SWOT analysis. Data collection techniques were carried out using observation, interviews and literature study techniques. Based on the research results, data was obtained that Merak Temple has various potentials that can attract tourists to visit it, including as a historical tourism destination, as a religious tourism destination, and its location is close to other tourist attractions. Apart from that, there are also strategies to make Merak Temple a tourist destination in Klaten Regency, including: promoting Merak Temple, creating an integrated tour package that covers all tourist attractions, completing public facilities to support tourism, adding road signs, renovating gates, providing education and outreach regarding important values ??to the community, providing out-of-class learning activities at cultural heritage sites in Klaten Regency, as well as improving the quality and quantity of public facilities that support tourist comfort, sustainable promotion.